Drilling and plombage (core decompression) of a femoral head avascular necrosis - Trc, T.; Chládek, P.; Havlas, V. (Osteologie, 2010)
The treatment of femoral head necrosis of adults is still rather problematic. Conservative treatment has been reported relatively unsuccessful and surgical treatment does not show convincing results either. The most effective seems to be a surgical treatment in early stages of the disease, however, the diagnosis still remains relatively complicated. For the late stages (2B and above) the most effective treatment option is represented by core decompression and vascular grafting. However, drilling and plombage (especially when using press-fit technique) seems to be successful, although not excellent. The authors describe their own method of drilling and plombage of the necrotic zone of the femoral head in 41 patients with X-ray detected necrotic changes of the femoral head. The pain measured by VAS was seen to decrease after surgery in all patients significantly. The Jacobs score was also observed to have increased (from fair to good outcome). We have not observed any large femoral head collapse after surgery, moreover, in some cases an improvement of the round shape of the femoral head was seen. It is important to mention that in all cases femoral heads with existing necrotic changes (flattening or collapse) were treated. Although the clinical improvement after surgery was not significantly high, the method we describe is a safe and simple method of diminishing pain in attempt to prepare the femoral head for further treatment in a future, without significant restriction of the indication due to necrosis (osteochondroplasty, resurfacing, THR).
Keywords: Avascular necrosis; femoral head; forage; core decompression; press-fit grafting